DEVELOPMENT OF HEALTH EDUCATION LEARNING USING CREATIVE PROBLEM SOLVING MODEL TO ENHANCE LEARNING ACHIEVEMENT AND COMMUNICATION SKILLS FOR SECONDARY SCHOOL STUDENTS - Phuakchaowai, Pichathon; Sarayuthpitak , Jintana; Rodpipat, Sarinya (Academic Journal of Thailand National Sports University, 2023)
Purposes: 1) To compare mean scores of learning achievement and communication skills before and after implementation of the experimental group and the control group, and 2) To compare the mean scores of learning achievement and communication skills after implementation between the experimental group and the control group. Method: The subjects were 80 secondary school students, divided equally into two groups: 40 of the experiment group students were assigned to study under the health education learning management using the creative problem-solving model and 40 of the control group students were assigned to study with the conventional teaching method. The research instruments were comprised of 8 health education lesson plans using the creative problem - solving model with an IOC of 0.83 The data collection instruments included learning achievements in the area of knowledge, attitude, practice and communication skills test with an IOC of 0.83, 0.94, 1, and 0.98. The duration of the experiment was 8 weeks. The data were analyzed by using mean, standard deviation and t - test. Results: 1) The mean scores of the learning achievement in the area of knowledge, attitude, practice and communication skills of the experiment group after learning were significantly higher than that before learning at the level of 0.05, and the mean scores of learning achievements in the area of knowledge of the control group after the implementation were significantly higher than that before at the level of 0.05, The mean scores of the learning achievement in the area of attitude, practice and communication skills of the control group after the implementation were not significantly higher than that before at the level of 0.05. Conclusion: The mean scores of the learning achievement in the area of knowledge, attitude, practice and communication skills of the experiment group after the implementation were significantly higher than that in the control group at .05 level.